Solar chimney model parameters to enhance cooling PV panel performance - Sh-eldin, Mohammed; Sopian, K.; O. Alghoul, Fatah; Abouhnik, Abdelnasser; M., Ae. Muftah (Canadian Centerof Science and Education, 2013)
The concept of using the Solar Chimney plays an important role in a wide range of topics to improve cooling system efficiency such as drying process, and single and multi-story buildings ventilation against temperature rising. In this paper, study the effective solar cooling chimney parameter model to enhance the performance of photovoltaic (PV) cooling system. First, a brief description of theoretical performance predictions of the solar cooling chimney also discusses the effect of the ambient wind velocity on the photovoltaic panel. Second, analysis air velocities at different points in solar cooling chimney are predicted and the temperature drop also estimated to predicted air velocities in the duct. Finally, from simulation result it was found for chimney height range 0.3 m - 3 m and at 60 oC, the air velocity increase from 0.6 to 1.78 m/s and Pressure difference between inlet and outlet increase from 0.5 to 5.3 KPa, which improve the PV panel voltage 8%.